Factors Associated With Reflective Practice Among Specialist Nurses in China: A Latent Profile Analysis - Lichun Xu; Liyu Lin; Aixuan Guan; Qingqing Wang; Feng Lin; Weicong Lin; Jing Li (Nursing Open)
ABSTRACT Aim The objective of this study was to investigate the level of reflective practice and its influencing factors among specialist nurses in Chinese tertiary general hospitals. Design A cross‐sectional study design was adopted. Methods A General Information Questionnaire and a Reflective Practice Questionnaire were distributed from July to August 2023 to specialist nurses who had obtained a Certificate of Nursing Practice, completed systematic specialist nurse training and were professionally qualified in six tertiary general hospitals in Xiamen, China. Results A total of 344 specialist nurses participated in the study. Specialist nurses' reflective practice was categorised into four potential characteristics. According to univariate analysis, reflective practice of specialist nurses was associated with marital status, participation in nursing consultations, feelings of lack of competence, perceived low patient recognition of specialist nurses, and perceived low physician recognition of specialist nurses. In the ordered logistic analysis, marital status and whether or not to participate in nursing consultations were influential factors in the reflective practice of specialist nurses. Conclusion Based on the results of this study, we recommend that nursing administrators should take some steps to improve reflective practice among specialist nurses.